Relaminarising fully turbulent pipe flow - Song, Baofang; Avila, Marc; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
We locally applied a control technique to relaminarise fully turbulent pipe flow at Reynolds numbers of up to 20,000. Downstream of the control point the flow remains laminar because of the linear stability of the basic flow and consequentely the drag is reduced substantially. At Re=20000 the pressure drop is reduced by an order of magnitude. We also applied a closely related control mechanism in experiments and managed to relmainarise turbulence at Reynolds number 6000 and the drag dropped by a factor of more than 3. The principal underlying the control scheme in experiments and simulations is closely connected to the self sustaining mechnism of wall bouned turbulence.
CRIS-Team Scopus Importer:2020-03-17